Ağız yanması sendromu - POLAT AKMANSOY, BERCESTE; ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2022)
Burning Mouth Syndrome (BMS) is a chronic pain and burning sensation in the mouth accompanied by various symptoms mainly seen in peri and postmenopausal women. Burning and stinging sensation on the tongue, lips and the other oral mucosal surfaces, dry mouth or increased salivation, taste change, loss of taste, paresthesia are the prominent symptoms. Idiopatic pain usually persists daily for more than 3 months. In this review, newest management approaches of BMS were presented and discussed.

Ağız Yanması Sendromu (AYS), yaygın olarak peri ve postmenapozal dönemdeki kadınlarda görülen çeşitli semptomların eşlik ettiği ağızdaki yaygın kronik ağrı ve yanma duygusudur. Semptomlar; dilde, dudaklarda ve diğer oral mukoza yüzeylerinde yanma ve batma duygusu, kuru ağız veya tükürük artışı, tat değişikliği, tat kaybı, parestezi duygusu olarak özetlenebilir. Bu semptomlar genellikle 3 aydan uzun süreli her gün devam eden idiyopatik kökenli ağrılardır. Bu çalışmanın amacı AYS konusundaki güncel tedavi yaklaşımları hakkında bilgi vermek ve tartışmaktır.
Burning mouth syndrome
Keywords: Ağız yanması sendromu; Kuru ağız; Dizestezi; Burning mouth syndrome; Dry mouth; Oral dysesthseia